Concordance in Aneurysm Size at Time of Rupture in Familial Intracranial Aneurysms. Issue 2 (February 2019) - Bourcier, Romain; Lindgren, Antti; Desal, Hubert; L'Allinec, Vincent; Januel, Anne Christine; Koivisto, Timo; Jääskeläinen, Juha E.; Slot, Emma M.H.; Mensing, Liselore; Zuithoff, Nicolaas P.A.; Milot, Geneviève; Algra, Ale; et al.
Abstract : Background and Purpose—: Intracranial aneurysm (IA) size and location are important determinants of aneurysm rupture risk. In familial IAs there is concordance of location; however, if such concordance exists for size is unknown. We analyzed the concordance of aneurysm size at time of rupture in familial IAs. Methods—: In pairs of affected relatives with aneurysmal subarachnoid hemorrhage, the ratio between the largest and the smallest aneurysm size at time of rupture was calculated. We also compared the proportion of families in which both IAs ruptured at a size < or ≥7 mm with the proportion of families in which one IA ruptured at <7 mm and another ≥7 mm. We calculated the repeatability with corresponding 95% CI for aneurysm size at time of rupture. Results—: About 130 patients from 64 families were included. Of the 68 affected pairs 18 (26%) had a ratio ⩽1.2, 38 (57%) had a ratio >1.2, and 12 (17%) had a ratio ≥3. We found no difference between the proportion of families (n=31; 49%) who both had IA at time of rupture <7 mm (n=20; 31%) or both ≥7 mm (n=11; 18%) and the proportion of those families with one patient with an IA <7 mm and another with an IA ≥7 mm (n=33; 51%; P =0.86). Overall, the repeatability in aneurysm size at rupture within familial IAs was 0.10 (95% CI, 0–0.35). Conclusions—: There is no good concordance in aneurysm size at rupture within familial IAs. These data suggest that size of a ruptured IA in a family member should not significantly impact on the management of a familial unruptured IA in a relative. Abstract : Supplemental Digital Content is available in the text.